PENGARUH PEMBERIAN PAKAN FERMENTASI DENGAN FORMULA YANG BERBEDA TERHADAP PERFORMA PENGGEMUKAN SAPI DI KAWASAN SEKOLAH PETERNAKAN RAKYAT (SPR) DESA NGADILUWIH, KECAMATAN NGADILUWIH, KABUPATEN KEDIRI - Dewi Damayanti; Didik Rudiono; Amiril Mukmin (Jurnal Ilmiah Fillia Cendekia, 2018)
Forty two cattles were kept for 21 days, to evaluated effects of different fermented rations using research operation. Nineteen were held in A pen while twenty three in B pen, and fed using A formula and B formula, respectively. Data were analizing using t test, and the parameters are included: feed quality, feedlot performance, and farmer perception. The result show that A formula consist of 64,64% DM; 9,13% CP; and 26,66% CF; while the other is 55,61% DM; 6,06% CP; and 41,02% CF. There are significant effect of ration (P<0,05) on ADG (1,28 kg/h/d vs 0,81 kg/h/d); DM consumption (14,62 kg/h/d vs 14,65 kg/h/d); FCR (12,53 kg/h/d vs 18,29 kg/h/d); and FER (8,76% vs 5,51%). There also difference perception among the farmers, especially on materials and the price. It’s conclude that A formula is betters than that B formula, but the both are need to be improved.